Edukasi Anemia dan Pemanfaatan Infused Water Herbal Sebagai Upaya Preventif Anemia Pada Siswi Kelas IX di Pondok Pesantren Az-Zahra Lampung Selatan - Fasya, Gyska Amelia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M), Institut Teknologi Sumatera, Lampung, Indonesia., 2023)
Anemia is the most common health problem suffered in the world. The prevalence of anemia is considered quite high, reaching 40-80% in adolescent girls. This will have a negative impact on the health condition and productivity of these teenagers. The age prevalence of anemia in Indonesia ranges from 13-18 years. Symptoms of anemia experienced can include dizziness, dizzy eyes, and pale palms. Currently, the prevention effort implemented is by using blood-boosting tablets. One herbal treatment that can be given is by using infused water which can meet fluid needs and provide nutrition. In this activity we carried out an educational program related to preventing anemia in young women at the Az-Zahra Islamic Boarding School, South Lampung.